Relasi Antara Omnibus Law di Era Pandemi Covid-19 Dan Perekonomian di Indonesia - Mohammad Orinaldi (Universitas Batanghari, 2020)
This research aims to determine the relationship between the omnibus law in the Covid-19 pandemic era and the economy in Indonesia. This research uses a qualitative approach with literature study methods. Researchers collect related data from journals, as well as internet sources related to research keywords. Furthermore, the researcher reduced the data and presented it in the form of scientific papers. The result of this research is that the omnibus law was drafted without adequate public consultation, leaving unions, civil society groups and academics unaware of its contents and forcing them to guess even the most controversial provisions. Even now the Omnibus law has begun to be implemented in the country's economic activities. One of the most damaging aspects of the law is its provision within the environmental family, which researchers believe is designed to expand the role of the central government and significantly reduce public participation in decision-making processes on environmental issues that will have a tremendous impact on the lives of surrounding communities. So, the pros and cons are still rolling and this law is deemed incapable of solving the country's economic problems because it is not a solution idea.